Factores de riesgo psicosociales en docentes de la Unidad Educativa Adolfo Valarezo - Guamán Huanca., Ruth Meline (2023)
Psychosocial risk factors refer to the working conditions present in an institution and that are related to the environment and personnel. The present investigation has as a general objective to analyze the psychosocial risk factors in teachers of the Adolfo Valarezo Educational Unit in orderto know the state of physical, mental and social health of teachers. The methods used were descriptive, cross-sectional and nonexperimental. For which instruments were applied in order tocollect data through the technique of a psychosocial risk assessment questionnaire used institutionally by the Ministry of Labor, which determined the level of risk of each of the factors,it was carried out a probabilistic sampling fulfilling various inclusion and exclusion criteria. Mostof the population studied were mestizo women, from 35 to 43 years of age; With third and fourthlevel studies between 3 to 10 years of work experience. Regarding the psychosocial risk factors ina global way, it was obtained that 75.7% present a low psychosocial risk of exposure and 24.3% amedium risk of exposure, that is, that the potential impact of the different psychosocial factors onsafety, health is low, therefore there is no risk factor in the educational unit studied and finally a psychoeducational proposal was developed for the teachers of said institution in order to maintain emotional and physical well-being, and thus increase the productivity and work performance, withsome guidelines for the authorities and departments in charge of looking after teachers and the institution